FOREIGN EXPERIENCE IN THE EFFECTIVE MANAGEMENT OF STATE ASSETS AND THE POSSIBILITY OF ITS APPLICATION IN UZBEKISTAN (World Economics and Finance Bulletin, 2022)
Considering the role and importance of state asset management, which has been growing in recent years, we have carried out analytical work, which showed how important state asset management is in the economy of any country. The experience of some foreign countries in the management of state assets, methods and approaches for its management were studied, conclusions and suggestions were made.
Keywords: State assets; market relations; state enterprises; privatization